2022
DOI: 10.1021/acssuschemeng.1c07631
|View full text |Cite
|
Sign up to set email alerts
|

Photocured Nanocellulose Composites: Recent Advances

Abstract: This perspective gives an overview of recent progress in the field of photocured polymer composites based on various forms of nanocelluloses, with a focus on cellulose nanofibrils. The manufacturing processes and performances of these nanocellulose composites are detailed, comprising solvent-assisted mixing processes, emulsification, coating and casting processes, preform impregnation, and 3D printing. Attention is also paid to life-cycle engineered approaches to improve their sustainability. These materials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 155 publications
0
14
0
Order By: Relevance
“…Recent advances in photocured composites containing cellulose nanomaterials, including those generated via 3D printing by stereolithography, have been extensively reviewed. 16 Those incorporating nanofibrils include aerogels and/or hydrogels for tissue engineering, 17,18 cell adhesion, 19 and complex-shaped 3D printed scaffolds. 20 The major challenge identified in incorporating TOCNFs is the hydrophilic nature of nanocellulose and its affinity for aggregation via hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in photocured composites containing cellulose nanomaterials, including those generated via 3D printing by stereolithography, have been extensively reviewed. 16 Those incorporating nanofibrils include aerogels and/or hydrogels for tissue engineering, 17,18 cell adhesion, 19 and complex-shaped 3D printed scaffolds. 20 The major challenge identified in incorporating TOCNFs is the hydrophilic nature of nanocellulose and its affinity for aggregation via hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…20 The major challenge identified in incorporating TOCNFs is the hydrophilic nature of nanocellulose and its affinity for aggregation via hydrogen bonding. 16 Accordingly, Sajab and coworkers showed that surface modification of CNF with PEO afforded enhanced mechanical properties to 3D printed composites. Polyurethanebased SLA resins modified with 3% CNF-PEO showed an increase in tensile strength (24%) and stiffness (10%), although weight loading above 3% CNF reduced the mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in photocured composites containing cellulose nanomaterials, including those generated via 3D printing by stereolithography, have been extensively reviewed . Those incorporating nanofibrils include aerogels and/or hydrogels for tissue engineering, , cell adhesion, and complex-shaped 3D printed scaffolds .…”
Section: Introductionmentioning
confidence: 99%
“…Those incorporating nanofibrils include aerogels and/or hydrogels for tissue engineering, , cell adhesion, and complex-shaped 3D printed scaffolds . The major challenge identified in incorporating TOCNFs is the hydrophilic nature of nanocellulose and its affinity for aggregation via hydrogen bonding . Accordingly, Sajab and co-workers showed that surface modification of CNF with PEO afforded enhanced mechanical properties to 3D printed composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation